Analysis of Human Factor Trends in Aircraft Accidents in Indonesia for The Period 2015-2024 - Muhammad Roil Billad; Alyssa Brilliani Suryanto Suryanto; Farid Baskoro; Dimas Arya Soeadyfa Fridyatama (Approach : Jurnal Teknologi Penerbangan, 2026)
This study aims to analyze the trend of Human Factor in aircraft accidents in Indonesia during the 2015–2024 period. Human Factor is an essential component of aviation safety because it relates to a person’s ability to make decisions, maintain situational awareness, communicate, and consistently follow procedures. This research uses a quantitative descriptive method with data collection techniques through document study of publicly available accident reports, as well as content analysis to identify Human Factor elements that appear in each case. The obtained data were coded into specific categories such as decision-making errors, loss of situational awareness, communication issues, fatigue, and procedural non-compliance, then calculated based on their frequency to observe patterns of change over the years. The results show that Human Factor remains a significant contributor to aircraft accidents, with an increasing trend in fatigue and decision-making aspects over the last five years. These findings emphasize the need for improved training, procedural oversight, and risk management to reduce the potential for human error in aviation operations in Indonesia